Development of pork adobo jerky - Landicho, Lilac G.; Villarino, Blanca J. (2010.)
ABSTRACT This study aimed to develop an acceptable pork adobo jerky. Three pork adobo recipes were tested for consumer acceptance using 50 randomly selected untrained panelists to determine the formulation to be utilized in producing the jerky. The most acceptable recipe was used to identify the appropriate drying time of the thinly sliced meat (about 3mm thick) at a constant temperature of 700C. The pork jerky samples were analyzed for moisture content, physicochemical, microbial and sensory tests. Additionally, standardization of the most acceptable pork adobo jerky was done. Among the different adobo recipes, the adobong Taal was found to be the most acceptable. Meanwhile, drying the pork adobo slices for 3 hours at 7000C produced the most acceptable product mainly on the basis of consumer acceptance test. It had a pH of between 4.3-4.5 moisture content of 24-27% (wet basis) and a water activity of 0.73-0.74. During the standardization, the products showed no significance differences (p>0.05) in terms of its moisture content, physicochemical, microbiological and sensory properties. Results manifested that drying pork slices for 3 hrs. at 700C can produce an acceptable and safe pork adobo jerky.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Pork adobo; Cookery (Pork)